Flying journey and the contemporary customers combating COVID-19: the 'need' of the hour. (26th July 2022) - Gupta, Riya; Agrawal, Rachna; Gupta, Arti
The rising competition of every sector has evolved innovative thinking and application of a more developed version of strategies. However, the emergence of COVID-19 has further amplified the struggles. The intense competition and declining profits of the Indian aviation sector are the major concerns to be discussed. This study focuses on finding the needs and preferences of flyers of the selected well-known companies. Convenience sampling has been used and data is collected from 217 respondents with the help of a structured questionnaire. Exploratory factor analysis (EFA) is used to make 22 variables into six significant factors. These factors are further confirmed with help of confirmatory factor analysis (CFA). The novelty of this study is to propose the realistic ground to guide the struggling aviation sector to achieve the dazzling wave of customers.